STUDY OF EFFICIENCY OF OIL REMOVAL OF WATER PRODUCED (PETROBRAS RN/CE) USING ADSORVENT MATERIALS - Isamar Alves de Sá; Ana Leticia Silva Costa; Emannuel Messias Fernandes Santos; Ana Karla Costa de Oliveira (The Journal of Engineering and Exact Sciences)
The management of water produced with oil (PW) is a major challenge for oil companies due to high volume generation and chemical complexity. It is necessary to treat it in order to minimize harmful effects to the environment through an appropriate treatment, allowing its reuse and, consequently, causing the least possible damage to the processes in which it will be used. The samples of contaminated water passed through three adsorbents: activated carbon (1.18mm), beach sand (2mm) and coconut shell in natura. The objective of this article is to compare the efficiency of the adsorption process in water contaminated with oil. The results showed the following efficiencies: 82% in the removal of turbidity when using the active charcoal, 95.90% in the removal of turbidity when using the sand of the beach and 38.38% in the removal of turbidity when using the coconut shell in natura.